Long‐Term Immunological Alterations in Bottlenose Dolphin a Decade after the Deepwater Horizon Oil Spill in the Northern Gulf of Mexico: Potential for Multigenerational Effects. (17th February 2021) - De Guise, Sylvain; Levin, Milton; Jasperse, Lindsay; Herrman, Jean; Wells, Randall S.; Rowles, Teresa; Schwacke, Lori
Abstract: Health assessments were conducted on bottlenose dolphins in Barataria Bay, Louisiana, USA, during 2011 to 2018, to assess potential health effects following the Deepwater Horizon oil spill, compared to the unoiled Sarasota Bay, Florida, USA, reference dolphin population. We previously reported significant increases in T‐lymphocyte proliferation, as well as lower T helper 1 (Th1) cytokines, higher Th2 cytokine IL‐4, and lower T regulatory (Treg) cytokine IL‐10 in Barataria Bay in 2011 compared to Sarasota Bay, consistent with Deepwater Horizon oil exposure. Although values between 2013 and 2016 were more similar to those observed in Sarasota Bay, T‐cell proliferation was again elevated and cytokine balance tilted toward Th2 in Barataria Bay during 2017–2018. In 2018, Barataria Bay dolphins had significantly more circulating Treg cells than Sarasota Bay dolphins. Mice experimentally exposed to oil also had significantly increased T‐lymphocyte proliferation and circulating Treg cell number, including effects in their unexposed progeny. In vitro stimulation resulted in greater Th2 responsiveness in Barataria Bay compared to Sarasota Bay dolphins, and in vitro oil exposure of Sarasota Bay dolphin cells also resulted in enhanced Th2 responsiveness. Evidence points to Treg cells as a potential target for the immunomodulatory effects of oil exposure. The immunological trends observed in Barataria Bay appeared exaggerated in dolphins born after the spill, suggesting the possibility of continued oil exposure or multigenerational health consequences of exposure to oil, as observed in mice. Environ Toxicol Chem 2021;40:1308–1321. © 2021 SETAC Abstract : Our study presents evidence of long‐term immune modulation following oil exposure in dolphins, including an increase in T lymphocyte proliferation and a shift of the cytokine balance toward a T helper 2 response, through the modulation of regulatory T cells, with mechanisms substantiated in a mouse model and via direct exposure of mouse cells to oil. The study also supports the potential for multigenerational immune health effects. Th1 = T helper 1; Treg = T regulatory cell.